E-government of village empowerment - Andira A.T.; Nguyen P.T.; Rema Devi S.; Shankar K.; Abadi S.; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
South Pringsewu is the name of a village located in Pringsewu district. This village has the main potential, namely agriculture and industry. To develop its potential it needs to be updated from the system that has been used in empowering the potential of the village manually and not yet using the information system even in the form of a website. The purpose of this research was to select South Pringsewu Village that has the potential of villages that need to be empowered using information technology. Information Technology is needed to facilitate the access, management and empowerment of village potentials, so that it is expected to be able to improve the progress and quality of South Pringsewu Village. The author conducted the research by observation, interview, and literature study methods and built web-based applications through the stages of planning, system analysis, system design and design, and system implementation using the PHP programming language. BEIESP.